Influence of hip joint simulator design and mechanics on the wear and creep of metal-on-polyethylene bearings. (May 2016) - Ali, Murat; Al-Hajjar, Mazen; Partridge, Susan; Williams, Sophie; Fisher, John; Jennings, Louise M
Hip joint simulators are used extensively for preclinical testing of hip replacements. The variation in simulator design and test conditions used worldwide can affect the tribological performance of polyethylene. The aim of this study was to assess the effects of simulator mechanics and design on the wear and creep of ultra-high-molecular-weight polyethylene. In the first part of this study, an electromechanical simulator and pneumatic simulator were used to compare the wear and creep of metal-on-polyethylene components under the same standard gait conditions. In the second part of the study, the same electromechanical hip joint simulator was used to investigate the influence of kinematics on wear. Higher wear rates and penetration depths were observed from the electromechanical simulator compared with the pneumatic simulator. When adduction/abduction was introduced to the gait cycle, there was no significant difference in wear with that obtained under the gait cycle condition without adduction/abduction. This study confirmed the influence of hip simulator design and loading conditions on the wear of polyethylene, and therefore direct comparisons of absolute wear rates between different hip joint simulators should be avoided. This study also confirmed that the resulting wear path was the governing factor in obtaining clinically relevant wear rates, and this can be achieved with either two axes or three axes of rotations. However, three axes of rotation (with the inclusion of adduction/abduction) more closely replicate clinical conditions and should therefore be the design approach for newly developed hip joint simulators used for preclinical testing.